Efektivitas Pembelajaran Digital Dengan Aplikasi Solar System Scope Terhadap Pemahaman Konsep Materi Tata Surya Pada Peserta Didik Kelas VI SD - Amelia Zalza Septiani; Wati Sukmawati (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the effectiveness of the Solar System Scope application in enhancing sixth-grade students’ understanding of solar system concepts. The research was conducted at SDN Pademangan Timur 05, Jakarta, involving 31 students from class VI. A one-group pretest-posttest design was used, in which students took a pre-test before and a post-test after using the application during learning. Data were collected through written tests to assess conceptual understanding, and were analyzed using descriptive and inferential statistics. The findings showed that the average pre-test score was 2.09 (41.8%) and the average post-test score increased to 4.56 (91.2%), resulting in an average improvement of 2.47 points. Statistical analysis indicated a significant difference between pre-test and post-test results (p < 0.05). These results suggest that the Solar System Scope application significantly improves students’ understanding of abstract astronomical concepts. Its interactive 3D visualization supports more effective science learning in elementary classrooms. The study highlights the potential of digital media as a valuable tool to support science education at the primary level.